2017
DOI: 10.1080/19440049.2017.1306883
|View full text |Cite
|
Sign up to set email alerts
|

New feed ingredients: the insect opportunity

Abstract: In the framework of sustainability and a circular economy, new ingredients for feed are desired and, to this end, initiatives for implementing such novel ingredients have been started. The initiatives include a range of different sources, of which insects are of particular interest. Within the European Union, generally, a new feed ingredient should comply with legal constraints in terms of 'yes, provided that' its safety commits to a range of legal limits for heavy metals, mycotoxins, pesticides, contaminants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 45 publications
0
41
0
1
Order By: Relevance
“…However, they could act as mechanical vectors of prions derived from at‐risk substrates of ruminant origin with potential concerns for humans or susceptible animals according to the destination of insect‐based products (EFSA, ). The current knowledge on the risk of prionic diseases posed by insects was recently reviewed by Van Raamsdonk, van der Fels‐Klerx, and De Jong (). In short, although prions cannot be expressed in insect genomes (Thackray et al., ), insects do appear to be able to act as vectors if reared on a contaminated substrate (Lupi, , ; Post, Riesner, Walldorf, & Mehlhorn, ).…”
Section: Prionsmentioning
confidence: 99%
“…However, they could act as mechanical vectors of prions derived from at‐risk substrates of ruminant origin with potential concerns for humans or susceptible animals according to the destination of insect‐based products (EFSA, ). The current knowledge on the risk of prionic diseases posed by insects was recently reviewed by Van Raamsdonk, van der Fels‐Klerx, and De Jong (). In short, although prions cannot be expressed in insect genomes (Thackray et al., ), insects do appear to be able to act as vectors if reared on a contaminated substrate (Lupi, , ; Post, Riesner, Walldorf, & Mehlhorn, ).…”
Section: Prionsmentioning
confidence: 99%
“…In light of the predicted increase in the world population by 2050 and the growing demand for high-quality protein sources for food and feed production, insect culture deserves special attention [1][2][3]. In fact, insects show a high protein and fat content, they can grow on organic by-products, their rearing is characterized by low environmental impact [4][5][6] as they produce low greenhouse gases and ammonia emissions [1,7,8], and they show low water and space requirements [5]. Among other insects, the black soldier fly (Hermetia illucens, HI Diptera, Stratiomydae) has been proposed by the European Food Safety Authority Scientific Committee [9] as one of the species with the greatest potential as food and feed ingredient in the European Union (EU).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that larvae of mealworm (Tenebrio molitor, Coleoptera Tenebrionidae) reared on olive fruits processing by-products can accumulate Pb and Hg [24], whereas Biancarosa et al (2018) [25] evidenced that HI grown on seaweed-enriched media accumulated significant amounts of PTEs such as Cd, Pb, and Hg. However, knowledge on chemical hazards associated to insects as potential ingredients for feed and food is scarce [9], but the interest about this topic is increasing [2,3,6,12,26,27]. Most studies used artificially-contaminated growth substrates to investigate the potential accumulation of PTEs in insects [28][29][30][31], and specifically in HI [20,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…A complete overview of the feed ban in the EU is reported in Thus far, the research carried out to evaluate the effects of dietary inclusion of insect-derived PAPs or dried larvae on in vivo performance, health status, and food product quality of fish and terrestrial monogastric species (poultry, swine) is promising. However, as for the other feed ingredients, well-defined protocols and controls of insect material productive chain must be implemented and regulated to protect animal and human safety (Ottoboni et al 2017b;van Raamsdonk et al 2017;Veys and Baeten 2018).…”
Section: Threatmentioning
confidence: 99%